Social Self-perception in Adolescents : Accuracy and Bias in their Perceptions of Acceptance/Rejection - Portillo, María; Fernández-Baena, Javier (Madrid : Colegio Oficial de Psicólogos de Madrid, 2020)
Social self-perception contributes to the development of social adjustment. Perception accuracy is associated with acceptance by peers, whereas inaccurate social perception has been linked to poor peer relationships, loneliness, and internalizing problems. The aim of this study was to analyze bias and both generalized and dyadic accuracy in adolescents perceptions of acceptance and rejection, and to examine the association with age, gender, and sociometric status. Participants were 206 adolescents (50.49% girls) aged between 12 and 19 years (M = 14.39, SD = 1.64). A sociometric test was administered. Results show that generalized perception accuracy was influenced by age, with older adolescents being more accurate. Gender differences were observed in generalized perceptions of rejection, with girls being less accurate. Regarding sociometric status, popular and rejected adolescents tended to underestimate the extent to which they were accepted and rejected, respectively. It is concluded that adolescents social self-perception vary according to age, gender, and sociometric status.
En inglés; resúmenes en español e inglés.
Descripción basada en metadatos suministrados por el editor y otras fuentes.
Descripción basada en Psicología educativa: revista de los psicólogos de la educación, vol. 26, n. 1 (enero 2020), P. 1-6.
Recurso electrónico. Santa Fe, Arg.: elibro, 2024. Disponible vía World Wide Web. El acceso puede estar limitado para las bibliotecas afiliadas a elibro.
Keywords: Aceptación entre iguales; Autopercepción social; Precisión perceptiva diádica.; Precisión perceptiva generalizada; Sesgo; Artículos electrónicos.